Atenção integral à saúde da mulher na transição para menopausa e pós-menopausa - Esposito, Isabel Cristina [UNIFESP] (2010)
Objective: To evaluate the factors that may influence the health of women during the menopausal transition and postmenopausal women as well as the primary attention actions with multiprofissional group in early and late postmenopause. Material e Methods: The Integral Attention Programme for climateric women (PIAC) of Menopausal transition and postmenopause outpatient section of Endocrinology Gynecology division of Gynecology Department of Federal University of São Paulo (UNIFESP). We elaborated two aims: Study I: Prospective and transversal section with multiprofissional group that applied IMK, WHQ, MSHQ and nutritional questionnaires. The total of participants were: menopausal transition (n= 48) and postmenopause (n=67) through verbal calling. The study was from June to August, 2006. Study II: propective Trial with orientation section of multiprofissional time and was evaluated using the medical history and physical examination as well as IMK and WHQ questionnaires. We included 69 patients divided into two groups: early postmenopause (n=32) and late postmenopause (n=37). The length of treatment was one year from January to December, 2007. Results: There is not a difference between menopausal transition and postmenopause in the clinical queries, functional capacity and quality of life in Study I. However, there was high carbohydrate consumption in postmenopause compared to menopausal transition. In Study II, We did not find any significant differences in the influence of primary attention action when compared early postmenopause to late one. However, there was a decrease in menopausal symptoms in late postmenopause group, mainly in vasomotor symptoms. Also, the improvement in physical parameters of both groups was observed without any amelioration in lipid and glucose profile as well as in the quality of life. Conclusion: Women during the menopausal transition and postmenopause had similar and inadequate health state in the analyzed parameters.